2014
DOI: 10.1136/sextrans-2013-051230
|View full text |Cite
|
Sign up to set email alerts
|

High-risk human papillomavirus viral load and persistence among heterosexual HIV-negative and HIV-positive men

Abstract: Objectives High-risk human papillomavirus (HR-HPV) viral load is associated with HR-HPV transmission and HR-HPV persistence in women. It is unknown whether HR-HPV viral load is associated with persistence in HIV-negative or HIV-positive men. Methods HR-HPV viral load and persistence were evaluated among 703 HIV-negative and 233 HIV-positive heterosexual men who participated in a male circumcision trial in Rakai, Uganda. Penile swabs were tested at baseline and 6, 12 and 24 months for HR-HPV using the Roche H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…[3] Evidence also suggests increased risk for HIV acquisition during infection with oncogenic HPV and persistent HPV infection is more common among men living with HIV compared to uninfected men. [5]…”
Section: Introductionmentioning
confidence: 99%
“…[3] Evidence also suggests increased risk for HIV acquisition during infection with oncogenic HPV and persistent HPV infection is more common among men living with HIV compared to uninfected men. [5]…”
Section: Introductionmentioning
confidence: 99%
“…First, STIs are comorbid: HPV and HBV co-occur. 78 They are also related to HIV 84,85 and other STIs. 86,87 Second, the comorbidity among STIs is not surprising in light of the common set of sexual risk behaviors that increases vulnerability to STIs.…”
Section: Sexually Transmitted Infections (Stis)mentioning
confidence: 99%
“…To our knowledge, only one study in Ugandan men has examined the association in penile HPV viral load and subsequent HPV clearance 15 . This study found that prevalent high viral load infections for high-risk HPV types were more likely to persist to 6 months and 12 months in comparison to low viral load infections in the glans.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between penile HPV viral load and the subsequent rate of HPV clearance in men remains unknown. To our knowledge, only one study in Uganda has examined the association between penile HPV viral load and HPV persistence; however, this study did not examine type-specific HPV viral load and only examined HPV infections in the glans anatomical site 15 .…”
Section: Introductionmentioning
confidence: 99%